Studies for IAA (Indole-3-Acetic Acid) Production by Isolates H6 with Nitric Acid Mutation - RAHAYU FITRIANI WANGSA PUTRIE; TIWIT WIDOWATI; HARMASTINI SUKIMAN (Microbiology Indonesia, 2017)
Nitric acid mutations are known could be used for strain improvement. This research aimed to studies IAA production by nitric acid mutan were compared with wild type. Mutation were conducted with some different treatment time such as 0, 30, 60, 90 and 120 min subsequently it were measured for IAA production. Isolate H6 as -1wild type isolates were also molecularly identified. The wild strain exhibited 53.83 µg mL of IAA while the -1 -1. nitric acid mutan within a range 77.39 µg mL to 95.70 µg mL Isolates H6.60 exhibited the highest IAA -1 production which 39.87 µg mL higher were compared with wild-type. Based on 16S rRNA gene analysis, isolate H6 belonged to Lysobacter sp. ES2-22.